Injury and Illness Trends in the National Hockey League Following an Abrupt Cessation of Play - Adam M Pinkoski; Matthew Davies; Mark Sommerfeldt; Dean T Eurich; Don Voaklander (International Journal of Sports Physical Therapy)
# Background